Analisis Algoritma Genetika dan Algoritma Monroe pada Penjadwalan Tenaga Kesehatan di Rumah Sakit H. Amri Tambunan Deli Serdang - Ade Guna Suteja; Muhammad Iqbal; Muhammad Syahputra Novelan (Jurnal Nasional Teknologi Komputer, 2026)
The study aims to analyze the influence of multimedia web interface design on the user retention rate on the Google Classroom e-learning platform at Universitas Pembangunan Panca Budi (UNPAB). Given the transition of digital learning systems within the campus environment, evaluating user experience becomes crucial for determining future platform standards. The research method used is quantitative with a causal associative approach. The research sample consists of 118 students from the Information Technology Study Program, class of 2022, selected using purposive sampling techniques. Data were collected through questionnairs with a Likert Scale and analyzed using simple linear regression via statistical software. The results showed that the interface design variable has a positive and significant effect on user retention with a t count value of 12,653 and a significance value of 0,000 (<0,05). The coefficient of determination (R2) indicates that interface design contributes 58,0% to user retention rate, while the remaining 42,0% is influenced by other factors outside the study. These findings confirm that intuitive and functional multimedia interfaces play a vital role in maintaining the sustainability of user interaction within digital learning management systems.